The Effect of Bait Types on the Catch of Bottom Long Line in Bantan Sari Village Bantan District Bengkalis Regency - Emiati, Emiati; Nasution, Polaris; Brown, Arthur (Department of Marine Science, Faculty of Fisheries and Marine Universitas Riau, 2022)
The main factor for the success of bottom longline fishing depends on the type of bait, both natural bait and artificial bait. The bait serves as an attractant for the target fish so that it is attracted to prey on it. In this study, the bait used was a machete, puput, and layur fish. The purpose of this study was to determine the amount, weight and type of catch based on the appropriate type of bait so that it can be a reference for fishermen for optimal use of bait in the operation of longline fishing gear. This research was conducted in February 2022, located in the waters of Bantan Sari Village, Bantan District, Bengkalis Regency. The method used is the experimental fishing method, by operating the fishing gear directly and analyzing using the analysis of variance and the Least Significant Difference test. Based on the research, the catches obtained were debuk fish, gelama, stingrays, and puffer, with the highest catches in terms of weight, namely stingrays as much as 61800 g